Pengembangan Kapasitas Pengelola Badan Usaha Milik Desa - Alkadafi, Muammar; Afrizal, Afrizal; April, Muhammad (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2023)
The purpose of this service is to increase the capacity of BUMDes managers and improve the performance of BUMDes institutions in Kuindra District, Indragiri Hilir Regency. The Service Method, using the Participatory Rural Appraisal (PAR) method. The PAR method prioritizes the participation of BUMDes managers consisting of the Director, Secretary, Treasurer of the BUMDes from 5 (five) villages that are the target of capacity building activities in the form of training. There are 3 (three) stages of activities carried out. First, pre-test, participatory discussion related to the constraints of BUMDes management. Second, transfer of knowledge to BUMDes managers. Third, post-test evaluation of the achievement of activities. The result of dedication. Capacity building for BUMDes managers in this service activity has succeeded in increasing the capacity of the individual, organizational and capacity levels in the BUMDes management system. At the individual capacity level, BUMDes managers already have knowledge about the duties and functions as managers. Skills in planning business units, making financial reports using Microsoft excel. Meanwhile, at the organizational and system level, there is a change in the management of BUMDes based on existing regulations, structuring institutional administration, making decisions through village deliberations. The service team suggested to BUMDes managers to utilize village funds (DD), Provincial financial assistance (BANKEU) effectively in supporting BUMDes business development, explore village potential for business unit development by conducting business feasibility studies first, collaborate between BUMDes to expand the BUMDes market.